Manifestations of the Electron-Phonon Coupling in the Spectroscopy of High-Temperature Superconductors - A. S. Mishchenko (Advances in Condensed Matter Physics)
A review of experimental and theoretical results on the spectroscopy of high-temperature superconductors is presented. The models where hole doped into antiferromagnet interacts both with magnetic subsystem and with phonons are considered. Theoretical results of these models for phonon spectra, angle resolved photoemission spectra, and optical conductivity are presented. Comparison with experimental data gives evidence for the strong electron-phonon coupling in the undoped and weakly doped high-temperature superconductors. The strength of electron-phonon coupling decreases with doping though at the optimal doping the compounds are still in the intermediate coupling regime.